Japan : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that Japan's economic recovery continued in 2003 and into the first part of 2004. For 2003, GDP growth reached 2 1\2 percent, double the mid-year consensus forecast, and continued at about 6 percent on an annualized basis in the first quarter of 2004. As the economic recovery broadens further, real GDP is projected to expand by 4 1\2 percent in 2004 and 2 1\2 percent in 2005, with CPI deflation ebbing to zero by the end of this period.